Teori Karl Marx dan Redistribusi Sumber Daya Pendidikan: Meninjau Manajemen Pendidikan yang Berorientasi Keadilan Sosial - Dilla Gusti Elfira; Silfia Hanani; Aisyah Syafitri; Muaddyl Akhyar; Nur Indri Yani Harahap (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Creating a social justice-orientated education system through resource redistribution will open the door for every individual to get a quality education and develop their full potential. This will help reduce social inequality in education, which in turn can have a positive impact on society and the economy as a whole. The purpose of this research is to explain about Karl Marx's Theory and Redistribution of Educational Resources: Reviewing Social Justice-Oriented Education Management. The method used in this study uses qualitative research procedures using a research approach in the form of a literature study. Sources of information in this study were reviewed from various novel sources of literature, research reports, scientific essays, theses, dissertations and posts both print and electronic related to Karl Marx Theory and Redistribution of Educational Resources: Reviewing Social Justice-Oriented Education Management. The results of this study show that applying Marx's theory in education management involves a number of concrete steps, including equitable resource allocation, free or affordable education, inclusion, critical education, the role of government, community participation, and quality evaluation. These are measures that aim to transform the education system into a powerful tool for reducing social inequality and ensuring that every individual has an equal opportunity to develop fully. Working towards social justice in education requires the co-operation of various parties, including governments, educational institutions, communities and individuals. Only with concerted efforts can we create an education system that empowers all individuals, without exception, to reach their full potential and build a more just and socially equitable society.